Diversifying Finance of Higher Education - Weidman, John C. (Education Policy Analysis Archives, 1995)
In countries throughout the world, there are increasing pressures to reduce the government share of costs for goods and services with high payoffs to individuals so that the limited available public funds can be used for other needs. This paper suggests several strategies for reducing government expenditures on higher education, including direct cost recovery, grants from and contracts with external agencies, income-producing enterprises, private contributions, and expansion of the private sector. Policy implications and examples (e.g., student access and financial aid, tax status of revenues from enterprises, deferred cost recovery) are presented for both developing and developed countries.